Efficacy of Single- and Double-Volume Exchange Transfusion for Neonatal Hyperbilirubinemia: Single- and Double-Volume Exchange Transfusion for Neonatal Hyperbilirubinemia - Xiong, Zhongzheng; Liu, Xianchuan; Li, Xiangzhu (Journal of Medical Biochemistry, 2023)
Background: To investigate the efficacy and safety of single- and double-volume exchange transfusion for neonatal hyperbilirubinemia (HB) and compare their effects on the internal environment of newborns. Methods: The clinical data of 96 HB newborns admitted to and treated in our hospitals from January 2016 to October 2021 were retrospectively analyzed. Then, these newborns were divided into single volume group (80-110 mL/kg, n=48) and double volume group (150-180 mL/kg, n=48) by the exchange volume per unit body mass. The hematological indicators [total serum bilirubin (TSB), peripheral blood red blood cell (RBC) count, white blood cell (WBC) count, platelet (PLT) count, serum albumin (ALB), prothrombin time (PT) and activated partial thromboplastin time (APTT)], and changes in inner-environment indexes (blood gas, blood glucose, acid-base and electrolyte levels) were compared between the two groups of newborns before treatment and after once treatment. Additionally, the adverse reactions of exchange transfusion in the two groups of newborns were recorded. Results: The mean exchange volume was (96.79±11.52) mL/kg and (160.74±10.19) mL/kg, and the exchange time was (98.66±19.86) min and (110.33±22.71) min in single volume group and double volume group, respectively. The differences were statistically significant (P=0.009). The average length of hospital stay was (9.14±3.78) d in single volume group and (9.75±4.05) d in double volume group, displaying no statistically significant difference (P=0.448). The total bilirubin (TBIL) and indirect bilirubin levels significantly declined after exchange transfusion compared with those before exchange transfusion (P=0.032), and they were significantly lower in double volume group than those in single volume group after exchange transfusion (P=0.007). The TBIL exchange rate was significantly higher in double volume group than that in single volume group [(58.60±3.73)% vs. (50.57±3.45)%, P=0.023]. Compared with those before exchange transfusion, the WBC count, PLT count, power of hydrogen (pH) value, HCO3- level, and serum sodium, serum potassium, serum calcium and serum ALB levels were significantly reduced, while RBC count, PT, APTT and blood glucose level were significantly increased after exchange transfusion. The hemoglobin (Hb) level, PaO2 and PaCO2 in the two groups after exchange transfusion showed no statistically significant differences from those before exchange transfusion (P>0.05). After exchange transfusion, double volume group exhibited a significantly decreased PLT count and a significantly raised blood glucose level in contrast with single volume group (P=0.019), and there were no statistically significant differences in the other indicators between the two groups (P>0.05). The exchange transfusion-related adverse reactions mainly included hyperglycemia, acid-base and electrolyte disorders, apnea, necrotizing enterocolitis (NEC) and heart failure. The newborns were all improved and discharged after symptomatic therapy. No statistically significant difference was found in the incidence rate of adverse reactions between the two groups (P>0.05). Conclusions: For neonatal HB, single-volume exchange transfusion has fewer effects on the internal environment of newborns, needs smaller blood consumption volume and shorter exchange time and can visibly lower the serum bilirubin level in comparison with double-volume exchange transfusion. Therefore, single-volume exchange transfusion has favorable value in clinical application.